Respuesta :

Answer:

  3. (x, y) = (3, 2)

  6. (x, y) = (10, 4/3)

  9. (x, y) = (-2, -1)

  12. (x, y) = (8, 3)

Step-by-step explanation:

3, 6. See the attachment. 3 is graphed in red/orange. 6 is graphed in blue, purple.

__

9. Use the expression for y in the second equation to substitute for y in the first equation:

  4(3x +5) -x = -2

  12x +20 -x = -2 . . . eliminate parentheses

  11x = -22 . . . . . . . .  subtract 20, collect terms

  x = -2 . . . . . . . . . . . divide by 11

  y = 3(-2) +5 = -1 . . .substitute for x in the second equation

The solution is (x, y) = (-2, -1).

__

12. Subtract 3/4x from the second equation to get an expression for y:

  y = 9 - 3/4x

Substitute that into the first equation:

  3(9 -3/4x) -5/4x = -1

  27 -9/4x -5/4x = -1 . . . . eliminate parentheses

  -14/4x = -28 . . . . . . . . . . collect terms, subtract 27

  x = 8 . . . . . . . . . . . . . . . . multiply by -4/14

  y = 9 -3/4(8) = 3 . . . . . . substitute into the expression for y

The solution is (x, y) = (8, 3).

Ver imagen sqdancefan
ACCESS MORE